A study to assess mother’s health seeking behaviour regarding oral rehydration solutions in diarrhoea in children 2 months to 5 years of age - Agarwal, Shachi; Anand, Shweta (International Journal of Contemporary Pediatrics, 2023)
Background: Diarrhoeal infections are the second leading cause of death worldwide in under-five children covering 9% of the total deaths. The objective of the study was to assess and compare mothers’ knowledge, attitude and practice of oral rehydration solutions (ORS) in diarrhoea in children. Methods: A cross-sectional hospital-based observational study was conducted in a tertiary centre amongst all 400 children between age group 2 months to 60 months admitted with acute watery diarrhoea. A pre-tested questionnaire and face-to-face interviews with the mothers was used as a data collection tool. Results: Most of the mothers 336 (84%) were 21-30-year-old, 150(37.5%) were illiterate, 74 (18.5%) were unemployed. 49% people came from rural background. The 250 (65%) mothers were aware about the role of ORS in diarrhea, 130 (32.5%) knew about the preparation of ORS and only 70 (17.5%) were aware about the ORS storage. Conclusions: Mother’s knowledge regarding management and prevention of diarrhea needs to be upgraded to allow better utilisation of health resources by the families.